KOMBINASI ALGORITMA BRANCH AND BOUND DAN CHEAPEST INSERTION HEURISTIC DALAM MENGOPTIMALKAN RUTE DISTRIBUSI KURIR PAKET JNT DI KECAMATAN BATANG CENAKU - Elfira Safitri; Sri Basriati; Winda Widiarti; Sri Sukmawati (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Traveling Salesman Problem (TSP) is a problem faced by salesmen who only visit each city once and then return to their hometown with the shortest distance. The aim of this research is to determine the shortest route for the distribution journey of JNT package couriers.The method used in this research is a combination of the Branch and Bound Algorithm and the Cheapest Insertion Heuristic. Data analysis was carried out by interpreting the problem in graph form, next use the Googling application to search and determine distances. Based on the research results, it was found that the shortest route for JNT package courier distribution District is JNT Belilas → Kuala Kilan → Bukit Lipai → Aur Cina → Pejangki → Petaling Jaya → Puntianai → Lahai → Talang Mulya → Talang Bersemi → Anak Talang → Kepayang sari → Alim 2 → Sipang → Alim 1 → Batu Papan → Cenaku Kecil → Pematang Manggis → Kerubung Jaya → Bukit Lingkar → Bukit Indah → Kuala Gading → JNT Belilas with total distance 172 km